Crashworthiness improvements of multi-cell thin-walled tubes through lattice structure enhancements - Liu, Hu (2021)
Taking advantage of multi-cell tubes and lattice structures on improving crashworthiness performances, a novel multi-cell thin-walled tube filled with uniform and graded lattice structures is explored in this paper. The body-centered cubic lattice structure is employed as the uniform lattice filler, while the graded lattice filler is constructed by varying the diameter of lattice rods in each layer. Several geometric parameters are investigated numerically, which include the cell number of tube, the dimension of tube and lattice, the height-to-width ratio of the enhanced tube, and the configuration of graded lattices. These parameters are then compared for their crushing load-displacement curves, deformation modes, and energy-absorbing mechanisms. It is observed that the multi-cell tubes exhibit significant improvements to the absorbed energy and crushing force efficiency over the single-cell tubes. In addition, the specific energy absorption (SEA) of the hybrid multi-cell tube structures is improved by 78.6% with respect to the sum of its individual constituents. Furthermore, the multi-cell tube structure filled with graded lattices can present larger energy-absorbing capacity than its uniform lattice counterpart, and the strong end at its top provides better SEA performance. Overall, the hybrid lattice-enhanced tube structure provides an optimal strategy for the crashworthiness design of multi-cell tubes, which can serve as a potential candidate for future crashworthiness applications.